3% polidocanol foam sclerotherapy versus hemorrhoidal artery ligation with recto anal repair in hemorrhoidal disease grades II-III: a randomized, pilot trial - Neves, Sara (2023)
Purpose: polidocanol foam sclerotherapy (SP) versus doppler-guided hemorrhoidal artery ligation with recto-anal repair (HAL-RAR) in the treatment of hemorrhoidal disease (HD) was analyzed. Methods: a prospective, randomized study including patients with HD grades II and III was performed. Participants were randomly assigned (1:1) into SP or HAL-RAR, during a recruitment period between September 2019 and February 2020. Therapeutic success (Sodergren’s and bleeding scores) was the primary outcome. Other outcomes evaluated included complications and implication in the professional life. Efficacy and safety outcomes were evaluated during the eight weeks after surgery or the final SP session. Results: forty-six patients were allocated either to SP (n = 22) or HAL-RAR (n = 24). Most patients achieved therapeutic success (SP 100 % vs HAL-RAR 90.9 %, p = 0.131). Complete success was higher in the SP group (91.7 % vs 68.2 %, p = 0.045) and SP patients had less complications (25 % vs 68.2 %, p = 0.003). HAL-RAR had a greater negative impact on work activity of the patient.